Potential herbicidal effect of synthetic chalcones on the initial growth of sesame, Sesamum indicum L., and brachiaria, Urochloa decumbens (Stapf) R. D. Webster - Gomes, Anabele Stefânia; Oliveira, Sarah Christina Caldas; Mendonça, Isabele Sena; da Silva, Cibele Carmo; Guiotti, Nicholas Xavier; Melo, Lennine Rodrigues; Silva, Wender Alves; Borghetti, Fabian (Iheringia, Série Botânica., 2018)
The search for and identifi cation of new molecules for the development of herbicides has grown in recent decades. With the objective of developing effi cient, environmentally friendly herbicides, we evaluated the phytotoxic activity of 13 synthetic chalcones on the development of sesame Sesamum indicum L. and brachiaria Urochloa decumbens (Stapf) R.D. Webster. Growth experiments were conducted at 30°C within a photoperiod of 12 hours. The positive control was distilled water whereas the negative control was the herbicide Glyphosate®. Two chalcones (3,13) signifi cantly inhibited the growth of the target species, being this inhibition comparable to that produced by Glyphosate®. The inhibitory eff ects of these chalcones on the growth of sesame and brachiaria deserves deeper investigation, since the methodology for their synthesis is simple and the reagents employed are of low cost, what make their large-scale production economically viable. Also, these molecules do not produce toxic residues such as those generated by synthetic herbicides.